Síntese, caracterização e avaliação de viabilidade celular de nanocristais de óxido de zinco, óxido de zinco dopados com cálcio e hidróxido de cálcio. - Souza, Gabriela Leite de (2019)
The objective of this research was to synthesize and characterize zinc oxide (ZnO), zinc oxide doped with different percentages of calcium (ZnO: X Ca; X = 0.7, 1.0, 5.0, 9.0) and calcium hydroxide (Ca (OH)2 - NC) nanocrystals. Furthermore, to evaluate ZnO and ZnO : X Ca on the viability of different cell models. The nanocrystals were synthesized and analyzed by the X-ray Diffraction (XRD) method and scanning electron microscopy (SEM) with energy dispersive X-Ray spectrometry (EDS). ZnO and ZnO : X Ca were solvated and evaluated at the concentrations of 10 μg/ml, 50 μg/ml and 100 μg/ml on the viability of RAW264.7 and SAOS-2 by MTT formazan and Alamar Blue. All data were statistically analyzed by One-Way ANOVA, followed by Tukey and Dunnett tests (α= 0.05). The data obtained by the XRD, SEM and EDS analyzes showed that the synthesized nanocrystals were characteristic of ZnO, ZnO:XCa and Ca(OH)2, with the size ranging from 20 to 80 nm. According to the characterization methods, all nanocrystals were successfully synthesized. ZnO, ZnO : 0.7 Ca and ZnO : 1.0 Ca presented the highest percentages of cell viability.